Absolute Globalization: The Way to Confront the Global Challenges - Ashik, Syod Ahsanul Islam; Afroje, Sahariya; Hossain, Nazmul (Advances in Social Sciences Research Journal, 2022)
The world is currently confronted with multidimensional challenges which are cause of concern for the earth’s all living creations. The most remarkable challenges are global warming and global climate changes, tremendous poverty, environment pollution, warfare, antibiotic resistance, migration problems, and the spread of contagious and deadly diseases etc. The adverse effects of these are very devastating. They will affect hydrology and biology of earth, everything including economy, eco-system, and the substances. The challenging factors are interconnected, and acceleration and minimization are interlinked. The study is to analysis the challenges the world is currently confronting with and their potential impacts, the reasons behind the challenges and the potential way to overcome the challenges. The study is based on secondary sources of data and information including scientific and academic journals, scholar articles, research papers, books, and other relevant sources to make a deep analysis, interpretation and re-interpretation and describe and explain the issue of this proposed study. The study recommends ‘Absolute Globalization’, an absolute integration of global economic, education, political, and social institutions where regionalism will be the cornerstone of the integration, as the way to confront the challenges.